1995
DOI: 10.1172/jci118367
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus-mediated gene transfer into normal rabbit arteries results in prolonged vascular cell activation, inflammation, and neointimal hyperplasia.

Abstract: Exposure of normal arteries to adenovirus vectors resulted in: (a) pronounced infiltration of T cells throughout the artery wall; (b) upregulation of intercellular adhesion molecule-i and vascular cell adhesion molecule-i in arterial smooth muscle cells; (c) neointimal hyperplasia. These findings were present both 10 and 30 d after gene transfer, with no evidence of a decline in severity over time.Adenovirus vectors have pleiotropic effects on the arterial wall and cause significant pathology. Interpretation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
173
6
2

Year Published

1998
1998
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 290 publications
(185 citation statements)
references
References 43 publications
4
173
6
2
Order By: Relevance
“…Additionally, the immunogenicity of the vector can produce local and systemic adverse reactions. [23][24][25] Therefore, we have examined the use of polymer carriers to facilitate gene delivery using plasmid DNA. The release of genetic material from intravascular stents could represent a new therapeutic modality 14 since, unlike balloon catheters, the stent remains within the vessel, avoiding the limitations associated with the delivery of large quantities of genetic material within a few minutes.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the immunogenicity of the vector can produce local and systemic adverse reactions. [23][24][25] Therefore, we have examined the use of polymer carriers to facilitate gene delivery using plasmid DNA. The release of genetic material from intravascular stents could represent a new therapeutic modality 14 since, unlike balloon catheters, the stent remains within the vessel, avoiding the limitations associated with the delivery of large quantities of genetic material within a few minutes.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the function of the transgene it is crucial that the vector itself does not alter the biological process being studied. It has recently been reported that the high adenoviral loads needed to achieve transgene expression have been associated with local inflammation after delivery into rabbit arteries 1 and the respiratory epithelium of both primates 2 and humans. 3 However, the precise mechanism underlying this inflammatory response remains obscure.…”
Section: Introductionmentioning
confidence: 99%
“…However, this is not without the complications of toxicity and immunogenicity and mediates a purely transient transgene expression when first-generation vectors are utilized. 7 Adeno-associated viruses (AAV) have been suggested as potential alternative vectors for vascular gene therapy due to their longevity of transgene expression and relatively favourable safety profile. AAV serotype-2 (AAV-2)-based vectors have been used for cardiovascular gene delivery locally into blood vessels 8,9 and by direct intra-myocardial injection, 10 the latter showing success therapeutically when delivered prior to surgical intervention, thereby allowing sufficient transgene to be expressed in the heart.…”
mentioning
confidence: 99%